Federal royal commissions in Canada, 1867-1966 : a checklist - Henderson, George F. (George Fletcher), 1936- (Heritage., 1967)
Checklist to Canadian federal royal commission reports [1868-, nos. 1-396]. Checklist for nos. 395- appear on the fiche.